Biopolymer gels as a basis of cryoprotective medium for testicular tissue of rats - Volkova, Nataliia; Yukhta, Mariia; Goltsev, Anatoliy (My University, 2018)
Cryopreservation of testis tissue is a promising approach to save fertility in prepubertal boys under going gonadotoxic cancer therapies. The using biopolymers as a basis of cryoprotective medium can be effective for the optimization of cryopreservation protocols of immature testicular tissue. The research purpose was to determine morphological parameters and metabolic activity of seminiferous tubules of immature rat testes under exposure to cryoprotective solution (DMSO) based on collagen or fibrin gels (CG or FG) as one of the first stages of developing the cryopreservation protocol. It was found that 30-min exposure of tissue samples to CG and FG with 0.6 M DMSO did not impair the spermatogenic epithelium and metabolic activity of the cells (MTT test and total lactate dehydrogenase activity). The use of FG at the time of exposure of 45 min did not lead to significant changes in the metabolic activity in contrast to other groups. The findings could be used to substantiate and develop the effective techniques for cryopreservation of immature seminiferous tubules.
Volkova N, Yukhta M, Goltsev A. Biopolymer gels as a basis of cryoprotective medium for testicular tissue of rats. Cell Tissue Bank. 2018 Dec;19(4):819-826. doi: 10.1007/s10561-018-9740-z. Epub 2018 Nov 21. PMID: 30465307.
Keywords: Immature testicular tissue; Spermatogenic epitelium; Spermatogenic epitelium; Collagen gel; Fibrin gel; Metabolic activity